2017
DOI: 10.1038/s41598-017-07180-1
|View full text |Cite
|
Sign up to set email alerts
|

Al-doped ZnO/Ag-nanowire Composite Electrodes for Flexible 3-Dimensional Nanowire Solar Cells

Abstract: Silver nanowires in conjunction with sputter-coated Al-doped ZnO (AZO) thin films were used as a composite transparent top electrode for hybrid radial-junction ZnO nanowire/a-Si:H p-i-n thin-film solar cells. Solar cells with the composite nanowire top contacts attained a short-circuit current density (Jsc) of 13.9 mA/cm2 and a fill factor (FF) of 62% on glass substrates while a Jsc of 13.0 mA/cm2 and FF of 62% was achieved on plastic substrates. The power conversion efficiency (PCE) of the 3-dimensional solar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…It is important to note that the contact of AZO/Au has not been investigated theoretically and experimentally, which can be used in solar cells. This had been reported in the Ag nanowire electrode on AZO by Pathirane et al [6].…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…It is important to note that the contact of AZO/Au has not been investigated theoretically and experimentally, which can be used in solar cells. This had been reported in the Ag nanowire electrode on AZO by Pathirane et al [6].…”
Section: Introductionsupporting
confidence: 68%
“…The annealing temperature plays a key role in electrical properties, which can affect the morphological structures and the hopping quantities [5]. For example, Pathirane et al [6] in 2017 investigated the effect of annealing temperature on the efficacy of the AZO/Ag nanowire junction, both structurally and electrically. In another work, Dalouji et al [7] studied the electrical conductivity of C-Ni composite films annealed at a temperature range of 300-800 °C, whose nanoparticle size and Ni concentration could be strongly affected by the annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low thickness of the active layer, nanostructured OPVs require precisely controlled fabrication process. Thus, most of the reported works about nanotextured designs have been focused on the transparent electrodes based on silver and copper nanowire arrays or theoretical studies on the architectural engineering of polymer solar cells, confirming the advantages of nanostructures in OPV devices . Furthermore, some groups fabricated OPVs with decent PCE on nanostructured transporting electrodes such as ZnO and ZnS nanowires and thus more systematic studies are required in this regard to enhance the light absorption in organic materials .…”
Section: Introductionmentioning
confidence: 98%
“…They also calculated the barrier height and ideality factor to be about 10 and 0.3 eV, respectively for Au/Al: ZnO devices. Pathirane et al [38] reported the AZO/Ag nanowire (NW) electrodes for solar cells with Ag NW coated on the AZO. However, the barrier height and ideality factor for this particular device were not reported.…”
Section: Introductionmentioning
confidence: 99%